1991
DOI: 10.2307/1938918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Substrate Quality on Element Mineralization in Six Arctic Soils

Abstract: We compared the effects of temperature on rates of microbial respiration, N mineralization, nitrification, and P mineralization in soils from six arctic ecosystems located along a toposequence on Alaska's North Slope. Soils from these ecosystems were incubated aerobically in the laboratory for 13 wk and at temperatures representative of field values during a typical growing season. Rates of C and N mineralization were insensitive to temperature between 3° and 9°C but increased by factors of 2 or more between 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
379
7
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 600 publications
(428 citation statements)
references
References 24 publications
41
379
7
1
Order By: Relevance
“…Both CO 2 and DOC export rates were higher in 0-20 cm than in deeper layers. This result was consistent with other studies (Biasi et al, 2014;Wang et al, 2013) and in agreement with the idea that older soil found in deeper layers contains higher proportions of "recalcitrant" carbon than younger soil at surface (Bosatta and Agren, 1999;Hogg et al, 1992;Knorr et al, 2005;Nadelhoffer et al, 1991). Under the condition of restricted temperature and O 2 (8°C-AN), Rs did not differ much among soils of different depths; under other three conditions where temperature and O 2 were not so restricted, however, CO 2 and DOC export rates were all substantially higher than those of the same depth in 8°C-AN condition.…”
Section: Variations Among the Whole Depth Profilesupporting
confidence: 93%
“…Both CO 2 and DOC export rates were higher in 0-20 cm than in deeper layers. This result was consistent with other studies (Biasi et al, 2014;Wang et al, 2013) and in agreement with the idea that older soil found in deeper layers contains higher proportions of "recalcitrant" carbon than younger soil at surface (Bosatta and Agren, 1999;Hogg et al, 1992;Knorr et al, 2005;Nadelhoffer et al, 1991). Under the condition of restricted temperature and O 2 (8°C-AN), Rs did not differ much among soils of different depths; under other three conditions where temperature and O 2 were not so restricted, however, CO 2 and DOC export rates were all substantially higher than those of the same depth in 8°C-AN condition.…”
Section: Variations Among the Whole Depth Profilesupporting
confidence: 93%
“…The results of our experiment suggest that the availability of high N and P as expected under global warming scenarios (Nadelhoffer et al 1991) will alter the competition between vascular plant species in peat bog ecosystems. The interactions between nutrient and competition treatments found for specific leaf area in C. vulgaris and biomass in V. oxycoccus show that competitive vigor increased at higher nutrient availability, which is in contrast with our hypothesis.…”
Section: Resultsmentioning
confidence: 78%
“…Temperature rise as expected under the global change scenarios is likely to increase mineralization rates (Nadelhoffer et al 1991). Consequently, a higher amount of soil nitrogen (N) and phosphorus (P) will become available for the vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…The net result of less vegetation cover and higher soil density are higher maximum temperatures in the top soil as a result of less isolation by vegetation and more decomposition of organic material as a result of these higher temperatures and less acidic conditions. Probably, soil moisture content also will be lower (less C, compression, evaporation, Dormaar et al, 1989;Johnston et al, 1971;Moorhead and Reynolds, 1993;Nadelhoffer et al, 1991;Swift et al, 1979;Seastedt et al, 1991).…”
Section: Grazing and Burning Practicesmentioning
confidence: 99%
“…Especially the strong P-fixation capacity in these volcanic soils seems to be an important factor but also immobilization by micro-organisms is high in cold climate ecosystems with high C/N and C/P ratios of organic matter (Enriquez et al, 1993;Moorhead and Reynolds, 1993). In general, micro-organisms have a high nutrient demand (Swift et al, 1979), and the decomposer subsystem is mentioned to be able to buffer the nutrient concentrations in some grassland ecosystems (Chapin et al, 1978;Nadelhoffer et al, 1991;Seeling and Zasoski, 1993).…”
Section: The Effect Of Grazing and Burning On Soil Characteristicsmentioning
confidence: 99%